Plant diversity based on pollen and spores morphology from sediment lake of Kedung Ombo Purwodadi - Retno Puspitasari; Sri Widodo Agung Suedy; Sri Haryanti (NICHE Journal of Tropical Biology, 2018)
Kedung Ombo Lake was an artificial lake that has formed since 26 years ago. Environmental has changed from the terrestrial environment into the aquatic environment, because of that the diversity of flora around the Lake Kedung Ombo was changed. The diversity of flora can be learned through the morphology of pollen and spores. Aimed of this study was to determine the diversity of plants based on the morphology pollen and spores that found in the Lake Kedung Ombo sediment. Sampling took by coring clay soil sediment in depth of 1 m, located near the outlet of Lake Kedung Ombo. Data were analyzed by making the morphology of pollen and spores description. The result showed that morphology of pollen and spores are found in the Lake Kedung Ombo sediment has a variety of shapes and sizes. The plant's diversity obtained are 25 taxa plants that were categorized into 3 taxa of arboreal pollen (AP), 9 taxa of non-arboreal pollen (NAP) and 13 taxa of spores. The dominance of taxa NAP is Celtis sp. (45,12%), this suggested that shrubs or not plant trees were more developed in Lake Kedung Ombo environment. The study concluded that the value of diversity index categorized as low and the value of similarity index categorized as high, it means that plant diversity was quite similar and there is no significant changes of diversity with their presence were quite stable.